Structural depth profile and nanoscale piezoelectric properties of randomly oriented Pb(Zr0.50Ti0.50)O-3 thin films - Lima, E. C. [UNESP]; Araujo, E. B. [UNESP]; Souza Filho, A. G.; Paschoal, A. R.; Bdikin, I. K.; Kholkin, A. L. (Iop Publishing Ltd, 2012)
The structural properties of Pb(Zr0.50Ti0.50)O-3 thin films with no preferential orientation were studied throughout the film thickness. An analysis on depth profile shows the existence of a significant (1 0 0) alignment near the film-electrode interface. Nanoscale piezoelectric measurements demonstrate the existence of a self-polarization effect in the studied films. An increase in this effect with film thickness increasing from 200 to 710 nm suggests that Schottky barriers and/or mechanical coupling near the film-electrode interface cannot be the main mechanisms responsible for the self-polarization effect in the studied films.